Settlement of investor-state disputes: Can states avoid arbitration? - Isabella Cannatà; Riccardo Loschi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Can states avoid lengthy and costly investor-state arbitration proceedings by entering into amicable settlements? While this is always possible in principle, data suggests that states struggle to do so. This Perspective discusses possible structural reforms for states to enable (and encourage) their officials to engage in meaningful settlement negotiations with investors.
Keywords: 330